Mozart's Sonata in C Minor K. 457: Classic Gems Analytical Journey Works of Wolfgang Amadeus Mozart - Thomas, Nathan (Universitas Negeri Surabaya, 2024)
Wolfgang Amadeus Mozart is a very well-known classical music composer. It doesn't matter whether you are a classical music enthusiast or just a casual listener. You would have heard about Mozart. This research delves into the intricate musical landscape of Mozart's Sonata in C Minor, employing a descriptive qualitative analysis to unravel the underlying structural form within the composition. Focusing on the examination of the sonata's score, the study aims to elucidate the organization and interplay of musical elements made by Mozart in shaping this enduring masterpiece. In conclusion, this research aspires to contribute valuable insights into the formal architecture of Mozart's Sonata in C Minor, unraveling the intricacies that define its structural integrity. The qualitative descriptive analysis offers a nuanced exploration of the musical score, providing a foundation for future scholarly discussions and fostering a heightened appreciation for the timeless artistry of Mozart. The findings of the research showed the musical intrigues of Mozart's Sonata in C Minor. In conclusion, the analysis not only enriches the existing literature but also presents implications for both theoretical and practical applications in musicology and performance practice.